Management of a Malaysian Hospitality Academic Programme: A Work-Based Learning Approach - Wei, Loi Min (2018)
Leading one of the Entry Point Project (EPP) of the Economic Transformation Plan, Malaysia Centre for Tourism and Hospitality Education (MyCenTHE) shared the concept of work-based learning academic programme to the higher education providers (HEP) and hospitality industry in Malaysia as a mean to improve hospitality education, producing targeted qualified output of 50,000 personnel annually. The concept is new to the Malaysian education system that is governed by Malaysian Ministry of Education with Malaysian Qualifications Agency (MQA) as the guardian of tertiary education quality. Work-based learning concept introduced by MyCenTHE programme structure is different from the specific standards and guidelines set by MQA, thus, changes in the management of hospitality programmes is expected and is challenging having to comply to the standards and guidelines. This research paper aims to find out “How can the hospitality academic programme in Malaysia, in terms of programme delivery, be managed differently with the introduction of work-based learning (WBL)?” Qualitative research methodology is used for this research, utilising both descriptive and exploratory research methodology to study the topic, including the introduction of work-based learning, higher education quality, outcome-based education (OBE) and hospitality education in general. Interview with higher education provider, hotel establishments and participating students were conducted on the participant’s experience with work-based learning The research found that the introduction of work-based learning concept by MyCenTHE indeed has some influence on the hospitality and tourism education in Malaysia, however, the lack of clear guidance from MyCenTHE in managing work-based learning programme, even though it introduced the concept has resulted in the less successful implementation of the work-based learning hospitality academic programme. MQA published Guidelines of Good Practice: Work-based learning only in late 2015, with emphasis on assessment methodology, years after work-based learning is introduced. The guideline is also found not harmonise with Programme Standards: Hospitality and Tourism published earlier. After much exploration, the research concluded that there is least impact of work-based learning methodology to the industry, or the management of the education programme because it is not adopted by higher education provider, thus, it does not bring significant change to the delivery of programme in Malaysia. However, the research strongly recommends the higher education providers, that has interest to pursue the delivery method, to make efforts to study and benchmark those institutions in foreign countries who have successfully implement work-based learning prior to their implementation.